The development of a truly electronic scholarly journal in a developing country : challenges, difficulties, and accomplishments - Costa, Sely Maria de Souza (2002)
This paper describes the methodology developed and the experience gained in the creation of a dynamic and interactive electronic scholarly journal in an environment with shortage of resources. The work described is based on the concept of extensive communication drew from the theoretical thought in both, communication and information sciences, as well as a hybrid model of the scholarly communication process and the socalled parallel publishing model. The main aim of the project is to provide a prototype, which could be used by existing print journals in humanities and social sciences in similar environments, for conversion into electronic versions. The methodology and strategies developed are an integral part of the prototype.